Cholangiocarcinoma in an American Rhea (Rhea Americana araneipes) - Rocha, Paulo Ricardo Dell'armelina [UNESP]; Lopes, Letícya Lerner; Arruda, Laura Peixoto de; Pescador, Caroline Argenta; Cruz, Raquel Aparecida Sales da; Colodel, Edson Moleta (Universidade Federal de Santa Maria, 2015)
Cholangiocarcinomas are neoplasms that originate from the bile duct epithelium. The present case described a cholangiocarcinoma in an adult female American Rhea (Rhea Americana araneipes) by means of gross, histopathology and immunohistochemistry. Irregular, firm, multifocal, yellow-white masses, measuring from 0.4 to 6cm in diameter were observed in both liver lobes. At the cut surface, multiple firm nodules filled with connective tissue were present. Microscopically, the neoplasia was composed of small, irregular, gland-like structures of neoplastic cells surrounded by connective tissue. The cells resembled epithelial cells of the hepatic biliary ducts. Neoplastic cells were positive for cytokeratin and negative for vimentin. This is the first report of a malignant fatal neoplasia in an American Rhea.

Colangiocarcinomas são neoplasias originárias do epitélio do ducto biliar. O presente caso descreve os achados macroscópicos, microscópicos e imuno-histoquímicos de um colangiocarcinoma em uma ema fêmea (Rhea americana araneipes). No fígado, massas irregulares, firmes, multifocais, de coloração amarelo-esbranquiçada, medindo de 0,4 a 6cm de diâmetro foram observadas em ambos os lobos. Ao corte, múltiplos nódulos firmes preenchidos por tecido conjuntivo foram observados. Microscopicamente, a neoplasia era composta de células pequenas, irregulares, semelhantes às células do epitélio biliar, que formavam estruturas glandulares. A imuno-histoquímica foi positiva para citoqueratina e negativa para vimentina. Este trabalho constitui o primeiro relato de uma neoplasia maligna fatal em uma ema.
Colangiocarcinoma em uma ema
Keywords: Cholangiocarcinoma; Rhea; Immunohistochemistry; Wildlife; Colangiocarcinoma; Ema; Imuno-histoquímica; Aves selvagens